THE ADVANTAGES OF SOLAR TRACKER / AS VANTAGENS DO SISTEMA SOLAR TRACKER - Lewandoski, Cristiano Fernando; Santos, Reginaldo Ferreira; Ikpehai, Augustine (International Journal of Environmental Resilience Research and Science, 2021)
Solar tracking systems allow greater efficiency of a photovoltaic system by continuously adjusting its position in relation to the sun, thus increasing the generation of electrical energy. The integration of photovoltaic solar tracking systems in a photovoltaic plant allows the energy needs of users to be met more widely in a smaller area. This integration is facilitated by the existence of technologies such as access to the Internet via Wi-Fi, which allows the development of systems to be included in the domain of “Cloud” and Automation 4.0. In this study, an "open circuit" solar tracker, the first of its kind designed in Brazil on a plant scale, was designed and developed, which runs the tracking algorithm in the service programmed in a PLC, which has a Wi-Fi module integrated. This study opens the possibility of integrating power generation systems in the Cloud domain, which among other things, allows constant monitoring of the system's behavior with Solar tracking